Employment status, psychological needs, and mental health: Meta-analytic findings concerning the latent deprivation model - Paul, Karsten Ingmar; Scholl, Hannah; Moser, Klaus; Zechmann, Andrea; Batinic, Bernad (Frontiers in Psychology, 2023)
Marie Jahoda’s latent deprivation model proposes that unemployed people have a worse mental health compared to employed people because they suffer from a lack of not only the manifest function of employment (earning money) but also from a lack of five so-called latent functions of employment: Time structure, social contact, collective purpose (i.e. the feeling of being useful to other people), status, and activity. In order to test the basic assumptions of this theory, a study based on meta-analytic methods was conducted. Results showed that employed people reported higher levels of all five latent functions, as well as the manifest function, compared to unemployed people. They also report more latent functions than people who are out of the labor force (OLF). Moreover, OLF-people reported more manifest and latent functions than unemployed people. Specific analyses for three OLF-subgroups found retired people to be almost as deprived of the latent functions (but not the manifest function) as unemployed people, while students were closer to employed people but still experienced some manifest and latent deprivation. For homemakers the effect sizes pointed in the expected direction but were not significant. Thus, the proposition that employment is the best provider of the latent functions was generally endorsed, although homemakers need further scrutiny in future studies. All latent functions, as well the manifest function, emerged as significant independent predictors of mental health when the influence of the other manifest and latent functions was controlled. Together, the dimensions in the model explained 19% of the variation in mental health.